Project management : a systems approach to planning, scheduling, and controlling - Kerzner, Harold (Hoboken, New Jersey : Wiley, 2017)
c
"This Twefth Edition of the bestselling "bible" of project managemen t maintains the streamlined approach of the prior editions and continue s to align with PMI's Project Management Body of Knowledge (PMBOK)"--
Includes bibliographical references and indexes.
Keywords: Agile project management; Project management; Project management -- Case studies